228 Radiological dynamics and resistance types in patients with advanced melanoma treated with anti-PD-1 monotherapy. (9th November 2020) - Bai, Xue; Kim, Michelle; Kasumova, Gyulnara; Si, Lu; Tang, Bixia; Cui, Chuanliang; Yang, Xiaoling; Wei, Xiaoting; Cohen, Justine; Lawrence, Donald; Freedman, Christine; Fadden, Riley; et al.
Abstract : Background: The SITC Immunotherapy Resistance Taskforce recently defined primary and secondary resistance to anti-PD-1 therapy, 1 yet there is little data that compares these two scenarios. In particular, detailed radiological dynamics of the different resistance types remain undescribed. Methods: We performed independent single-blind reevaluations of available radiological image data on a retrospectively assembled cohort of advanced melanoma patients (n=254, median follow-up 31.3 months, figure 1) treated with anti-PD-1 monotherapy initiated between Sept 2009 and Aug 2018 at both Massachusetts General Hospital and Peking University Cancer Hospital. Radiological characteristics and timing at multiple crucial radiological landmarks were analyzed and correlated with each other and with survival. As per the SITC Taskforce, primary resistance was defined as a best response of stable disease (SD) lasting less than six months or disease progression (PD), secondary as PD following an initial partial or complete response (PR/CR) or SD lasting 6 months or greater. 1 Results: The most dramatic tumor reduction occurred within the first 3 months after anti-PD-1 initiation. A subpopulation of patients who had SD (28.6%, all with tumor shrinkage) experienced further tumor reduction and upgraded to CR/PR and 11.1% of patients with initial PR upgraded to CR. No patients without tumor shrinkage at the initial evaluation ultimately responded. Baseline tumor burden, response depth, timing of maximal response and PD pattern demonstrated great variation and were significantly correlated with each other and with survival. In multivariate analyses, deeper response depth was independently associated with a less widespread progression pattern, less involved organs, smaller target lesion size and slower tumor growth rate (all P≤.001) at PD, and longer post progression survival (PPS) (P=0.005). Compared to primary resistance, secondary resistance was correlated with less broad progression pattern, less tumor burden and slower tumor growth (all P≤.001). Patients with secondary resistance were more likely to receive further local/regional therapy (46.5% vs. 30.9%, P=0.07) rather than systemic therapy (27.9% vs. 56.9%, P<0.001), yet had a significantly longer PPS (HR 0.503, 95% CI, 0.288–0.879, P=0.02). Median PPS was not reached (95% CI, 11.8 months to not reached) for patients with secondary resistance and was 10.3 months (95% CI, 7.7–16.1) for patients with primary resistance (figure 2). Conclusions: Radiological dynamics were heterogeneous, yet significantly correlated with survival. Patterns of progression and PPS of the SITC Immunotherapy Resistance Taskforce defined primary and secondary resistance are different. This distinction may be important for the design of clinical trials targeting a PD-1 resistant population. Ethics Approval: This study has been conducted in compliance with local Institutional Review Board policies. Consent: NA. Reference: Kluger H, Tawbi H, Ascierto M, et al. Defining tumor resistance to PD-1 pathway blockade: recommendations from the first meeting of the SITC Immunotherapy Resistance Taskforce. J Immunother Cancer . 2020; 8:3000398.